Acne Scars: Pathogenesis, Classification and Treatment. (30th September 2010) - Fabbrocini, Gabriella; Annunziata, M. C.; D'Arco, V.; De Vita, V.; Lodi, G.; Mauriello, M. C.; Pastore, F.; Monfrecola, G.
Abstract : Acne has a prevalence of over 90% among adolescents and persists into adulthood in approximately 12%–14% of cases with psychological and social implications. Possible outcomes of the inflammatory acne lesions are acne scars which, although they can be treated in a number of ways, may have a negative psychological impact on social life and relationships. The main types of acne scars are atrophic and hypertrophic scars. The pathogenesis of acne scarring is still not fully understood, but several hypotheses have been proposed. There are numerous treatments: chemical peels, dermabrasion/microdermabrasion, laser treatment, punch techniques, dermal grafting, needling and combined therapies for atrophic scars: silicone gels, intralesional steroid therapy, cryotherapy, and surgery for hypertrophic and keloidal lesions. This paper summarizes acne scar pathogenesis, classification and treatment options.